2015
DOI: 10.1016/j.antiviral.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiotic Lactobacillus administered post-exposure averts the lethal sequelae of respiratory virus infection

Abstract: We reported previously that priming of the respiratory tract with immunobiotic Lactobacillus prior to virus challenge protects mice against subsequent lethal infection with pneumonia virus of mice (PVM). We present here the results of gene microarray which document differential expression of proinflammatory mediators in response to PVM infection alone and those suppressed in response to Lactobacillus plantarum. We also demonstrate for the first time that intranasal inoculation with live or heat-inactivated L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 76 publications
6
58
0
Order By: Relevance
“…Cytoplasmic NOD2 senses muramyl-dipeptide, a metabolite of extracellular bacterial peptidoglycan [41, 42], and can generate inflammatory responses that have been best characterized at the gastrointestinal mucosa [43]. We have also identified NOD2, along with TLR2, as the two principal receptors interacting with Lactobacillus at the respiratory mucosa [23; T. A. Rice, T. A. Brenner, et al , ms in preparation] suggesting that this PRR is of broad interest to the study of host-microbe interactions, including those mediated by AMs.…”
Section: 0 Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytoplasmic NOD2 senses muramyl-dipeptide, a metabolite of extracellular bacterial peptidoglycan [41, 42], and can generate inflammatory responses that have been best characterized at the gastrointestinal mucosa [43]. We have also identified NOD2, along with TLR2, as the two principal receptors interacting with Lactobacillus at the respiratory mucosa [23; T. A. Rice, T. A. Brenner, et al , ms in preparation] suggesting that this PRR is of broad interest to the study of host-microbe interactions, including those mediated by AMs.…”
Section: 0 Results and Discussionmentioning
confidence: 99%
“…Using recombinant PVM (rK2-PVM) which incorporates the sequence encoding the far-red fluorescent protein, mKATE2, we have recently shown that AMs are a primary leukocyte target for this virus, and that AMs support both virus replication and productive infection in vivo [19]. Furthermore, application of immunobiotic Lactobacillus species to the respiratory tract, a regimen that results in robust and sustained survival in response to virus infection [20 – 23] limits PVM infection and virion release from AMs [19]. …”
Section: 0 Introductionmentioning
confidence: 99%
“…However, and surprisingly, we found that Lp -mediated protection against lethal PVM infection was maintained in both TLR2 βˆ’/βˆ’ and NOD2 βˆ’/βˆ’ single gene-deleted mice (Percopo et al , 2015). Here, we utilize both NOD2 βˆ’/βˆ’ TLR2 βˆ’/βˆ’ double gene-deleted mice and a novel NOD2-TLR2 bifunctional ligand to demonstrate that the coordinate engagement of these PRRs contributes substantially to survival in response to an acute respiratory virus infection as well as to suppression of virus-induced inflammation.…”
Section: Introductionmentioning
confidence: 89%
“…Our group has shown that L. plantarum ( Lp ), both live and heat-inactivated (in the latter form as a paraprobiotic (Taverniti & Guglielmetti, 2011)), when administered directly to the respiratory tract, results in robust and sustained protection against the lethal sequelae of PVM infection. We have shown that Lp is not primarily an antiviral agent (Gabryszewski et al , 2011); the beneficial impact of Lp -administration is primarily via suppression of local inflammation (Gabryszewski et al , 2011; Garcia-Crespo et al , 2013; Percopo et al , 2014; Percopo et al , 2015). Lactobacillus -mediated protection against respiratory virus infection is a profound example of heterologous immunity (also known in other contexts as trained immunity or innate memory (Levy & Netea, 2014; Netea et al , 2011; Wissinger et al , 2009; Locati et al , 2013; van der Meer et al , 2015) a state in which a host’s interaction with a primary infectious or inflammatory stimulus alters the immune response to a distinct, or unrelated agent.…”
Section: Introductionmentioning
confidence: 99%
“…Lactobacillus-mediated priming of the respiratory tract also results in the profound suppression of a specific subset of proinflammatory cytokines (20,68), which may alter the responses of AMs in vivo (and perhaps not ex vivo, as discussed further below).…”
Section: Rice Et Al Unpublished Data)mentioning
confidence: 99%